Estudo comparativo de biomarcadores no transtorno depressivo maior em idosos e na doença de Alzheimer - Natália Silva Dias (2022)
Major depressive disorder (MDD) and Alzheimer's disease (AD) are prevalent conditions in the elderly population. Depressive disorders in elderly people have been identified as a risk factor or prodrome of AD, which possibly reflects the neurodegenerative processes common to these two conditions. It is important to establish a set of biomarkers for the investigation of the relationship between MDD and AD. This study’s purpose is to compare the performance in cognitive tests and the levels of cerebrospinal fluid biomarkers of a group of elderly people with MDD and a group of elderly people with mild AD dementia (ADD). Twenty subjects with MDD, twenty with AD and twenty controls were included in this research. Each one of them was submitted to cognitive assessment and cerebrospinal fluid puncture. Biomarkers for AD and inflammatory markers found in the fluid were evaluated. In the statistical analyses, the initial groups and subgroups were considered, besides comparisons of cognitive performance and inflammatory markers in the fluid, correlation analyzes, and multivariate models were performed. Cognitive assessments did not prove to be a good tool to differentiate elderly people with MDD from elderly people with ADD who present cognitive complaints. Aβ42 and p Tau181 were correlated with cognitive performance. The results of the present study suggest that IL-1ra has a neuroprotective effect and CCL11 is related to early events associated with neurodegeneration.